Stabilization of decision threshold for BER improvement using double carrier modulation/differential detection for outdoor optical wireless communications - Hitam, Salasiah; Abdullah, Mohamad Khazani; Wan Adnan, Wan Azizun; Sahbudin, Ratna Kalos Zakiah (Praise Worthy Prize, 2009)
A new transmission and detection technique namely Double Carrier Modulation/Differential Detection (DCM/Diff.D) for outdoor optical wireless (OW) is proposed. The technique employs two beams, one modulated with the data, the other with the inverted version of the same data. A differential detection technique is used at the receiver whereby the inverted data are used as the reference to perform the decision making, as opposed to the fixed threshold used in conventional technique. The probability of error under threshold instability in DCM/Diff.D technique and Intensity Modulation/Direct Detection (IM/DD) technique, is compared. A simulation under heavy rainfall condition of 8.33x10-4 cm/sec at bit rate of 2.5 Gbps with 0 dBm of optical transmitter power shows that this technique achieves an improvement of more then twice of distance of the conventional IM/DD.